Rabbit intestinal glycoprotein receptor for Escherichia coli heat-labile enterotoxin lacking affinity for cholera toxin. - Holmgren, J (1982)
The receptors for cholera toxin and Escherichia coli heat-labile toxin (LT) in rabbit small intestinal epithelium were characterized and compared. (i) In vivo studies in ligated intestinal loops showed that whereas LT B subunits could block the fluid secretogenic action of purified LT as well as cholera toxin, cholera toxin B subunits did not inhibit the LT response even when tested in a concentration 100-fold higher than one which gave complete blocking of cholera toxin action. (ii) In vitro studies indicated that isolated intestinal epithelial cells or brush-border membranes could bind about 10-fold more of E. coli LT than of cholera toxin. (iii) All binding sites for cholera toxin in duodenal, jejunal, or ileal mucosal cells or brush-border membranes were extracted by chloroform-methanol-water (4:8:3), which removed lipids quantitatively but did not extract glycoproteins. The extracted cholera toxin binding sites were to greater than 95% recovered in a monosialoganglioside fraction; quantitatively these sites closely corresponded to the concentration of chromatographically identified mucosal GM1 ganglioside (1 nmol of cholera toxin was bound per 1 to 2 nmol of GM1). In contrast, a substantial fraction of mucosal binding sites for E. coli LT remained in the delipidized tissue residue, and these sites had properties consistent with a glycoprotein nature. Thus, whereas cholera toxin appeared to bind highly selectively to GM1 ganglioside receptor sites of rabbit small intestine, E. coli LT bound both to GM1 ganglioside and to a main glycoprotein receptor for which cholera toxin lacks affinity.